Attitudes of future preschool educators about parental competencies - Sandra Kadum (Taylor & Francis Group, 2021)
The early childhood is the period when parents have the greatest influence on the upbringing of their child. In order to act positively in the upbringing of their own child, parents must be competent. Being competent means to have knowledge, be efficient and skilled in realizing certain forms of behaviour and to achieve results that are expected of it. Parents are expected to develop all socially desirable and positive traits in the child. In this process, parents are seeking support from the preschool teachers because they have the greatest interaction with them when they leave the child in the educational institution. That was exactly the point in this research i.e. we wanted to see whether future educational workers are trained and whether parents make mistakes in the upbringing of their children. 347 students of the preschool education studies in Pula, Koper and Maribor were questioned. The results indicate that our respondents noticed that parents have problems in the relationships with their children because they do not have enough knowledge to access their own child and ‘blame’ the TV/media and the peers for it.